Synthesis of Some Amino-oxy, Biguanidino-oxy and Piperazinyl Deriavatives of Propane via reaction between n-Hydroxyphthalimide and Epichlorohydrin - Mehta, Deepika; Talesera, G.L. (Asian Journal of Chemistry, 2010)
2,3-Epoxypropoxyphthalimide (III) was prepared by condensation of epichlorohydrin (II) with n-hydroxyphthalimide (I) when refluxed for a short time in presence of sodium hydride but produced bis-phthalimidoxy- 2-hydroxypropane (IV) when refluxed for a long time. Hydroxy group was replaced by chlorine and subsequent reaction with N-hydroxyphthalimide gave triphthalimidoxypropane (VI) derivative. Hydrolysis of 1,2,3-triphthalimidoxypropane in acidic media produced triamino-oxy trihydrohalide salt of propane (VII). Condensation of polyarnino-oxy compound with various para substituted dicyandiamide gave corresponding biguanidinooxy compounds (VIIIa-b).